2022
DOI: 10.1039/d1nr06211e
|View full text |Cite
|
Sign up to set email alerts
|

A laser-driven optical atomizer: photothermal generation and transport of zeptoliter-droplets along a carbon nanotube deposited hollow optical fiber

Abstract: This paper presents a novel atomizing methodology along the single strand of an optical fiber integrated with single-walled carbon nanotubes. Based on this photonic device, numerous droplets generation with zeptoliter volume scale was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…2010; Mei & Brydegaard 2015) or in optical atomisation techniques that can be applied to the production of airborne transported microdrops used as drug carriers (Lee et al. 2022). At the heart of all of these research fields is the injection of high-power photons into a small liquid sample, the initiation of phase transition from liquid to vapour, the rapid pressure fluctuations and the successive complex fluid mechanics driven by this impulsive energy input.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010; Mei & Brydegaard 2015) or in optical atomisation techniques that can be applied to the production of airborne transported microdrops used as drug carriers (Lee et al. 2022). At the heart of all of these research fields is the injection of high-power photons into a small liquid sample, the initiation of phase transition from liquid to vapour, the rapid pressure fluctuations and the successive complex fluid mechanics driven by this impulsive energy input.…”
Section: Introductionmentioning
confidence: 99%
“…Phase explosion in confined liquid volumes has recently gained interest because of its connection with thriving research areas like x-ray liquid crystallography (Grünbein et al 2021), x-ray holography (Hagemann et al 2021;Vassholz et al 2021), extreme UV light and plasma generation (Favre et al 2002). A better understanding of the interaction of high-power lasers with small liquid particles is also relevant in laser-based atmospheric monitoring techniques (Rohwetter et al 2010;Mei & Brydegaard 2015) or in optical atomisation techniques that can be applied to the production of airborne transported microdrops used as drug carriers (Lee et al 2022). At the heart of all of these research fields is the injection of high-power photons into a small liquid sample, the initiation of phase transition from liquid to vapour, the rapid pressure fluctuations and the successive complex fluid mechanics driven by this impulsive energy input.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that optical atomizers employing single-walled carbon nanotubes (SWCNTs) reliably operated with laser powers below 20mW. 4 In contrast, our optical atomizer with a metal film demonstrated remarkable thermal stability, implying its ability to withstand higher laser powers, thus enabling ejection at elevated laser power levels. This improved device stability enhances its suitability for high-power applications, making it particularly well-suited for demanding scenarios that necessitate higher laser powers.…”
Section: Resultsmentioning
confidence: 89%
“…In today's scarcity of freshwater resources, SIE technology is becoming attractive extremely. [21][22][23][24] In the last decade, along with the rapid boom of new nanomaterials such as graphene oxide (GO), [25][26][27][28] reduced graphene oxide (rGO), [29][30][31][32][33] carbon nanotube (CNT), [34][35][36] and various efficient photothermal structure designs, the efficiency of SIE can still reach 90% even at low solar concentration. New photothermal nanomaterials can achieve excellent broad-spectrum absorption and can convert solar energy into heat efficiently, making a qualitative leap in the traditional thermal distillation process and becoming a green and environmentally clean water production technology.…”
Section: Introductionmentioning
confidence: 99%